Sønnetapene: Lyriske sorguttrykk i Nick Caves «Skeleton Tree» (2016) og Naja Marie Aidts Har døden taget noget fra dig så giv det tilbage (2017) - Nesby, Linda Hamrin (K&K - Kultur og Klasse, 2019)
In 2015 and 2016, the sons of Australian singer and songwriter Nick Cave and of the Danish author Naja Marie Aidt both died in fall accidents related to substance-induced psychosis. Subsequently, Cave released the album “Skeleton Tree” (2016) and Aidt published the book “Har døden taget noget fra dig så giv det tilbage” (If death has taken something from you, then give it back) (2017), which can both be linked to how they worked through the deaths of their sons. This article discusses how texts with a similar topic can appear so different in form, and how they portray different ways of coping with the grieving process. Neither of the texts are poetry per se, but both use lyrical forms of expression that make it pertinent to use a poetic analysis approach. Cave’s song lyrics and Aidt’s poetic prose both express experiences where the use of various lyrical effects in a musical and visual context reveals different ways of dealing with grief. In both cases, repetition is a key aspect. This article shows how Skeleton Tree and If death has taken something from you, then give it back represent the elasticity of contemporary poetic writing that makes the genre suitable to render strong emotional experiences.